Diaphragm action in light steel framing by sheathing boards. (1st October 2020) - Lawson, R.M.; Kermani, A.; Stergiopoulos, M.; Coste, G.; Way, A.
Highlights: Tests on shear diaphragms with OSB/3 boards demonstrate good structural performance. Tests compare well with elastic model using a fixing shear stiffness of 1.1 kN/mm from push tests. Tests were calibrated against finite element model using non-linear characteristics of fixings. Development of a design method for diaphragm action of light steel shear walls. Development of approximate method to include combined stiffness of boards and X-bracing. Abstract: This paper presents the results of shear tests on light steel walls with two types of higher specification OSB/3 board and comparison with elastic theory based on the fixing shear stiffness. The tests were performed to BS EN 594 and showed that the design shear resistance was determined as 5.1 kN/m wall length for a limiting deflection of 0.003H or 4.3 kN/m for a limiting deflection of H/500, where H is the wall height. With plasterboard on the opposite face, the shear stiffness increased by 29%, but these results were more variable. For a single test on a wall with the OSB/3 board on one side and X bracing on the opposite face, the design shear resistance is 5.6 kN/m for a limiting deflection of H/500. For a flame retardant form of OSB/3 board, the stiffness was 21% higher than for the first series of OSB/3 tests. An elastic theory is presented to determine the limiting shear force as a function of the shear stiffness of the fixings between the boards and the C sections, which was provided from small-scale push tests. The results are compared with finite element models and a comparison with the test configurations is presented.